THE ROLE OF ZAKAT IN BUSINESS DEVELOPMENT OF SMES (STUDY ON BAZNAS SEMARANG, CENTRAL JAVA, INDONESIA) - Fatmasari Sukesti; Mamdukh Budiman (IJIBE (International Journal of Islamic Business Ethics), 2018)
Poverty in developing countries including Indonesia still an unresolved phenomenon. The distribution of assistance through productive zakat is believed to be one of the solutions in alleviating poverty by giving zakat which used for working capital of small and medium-sized businesses. This study examined the role of productive zakat given to SMEs in the city of Semarang through the Badan Amil Zakat Nasional (BAZNAS) Semarang. The result showed that productive zakat had significant positive effect on business development of SMEs. The value of R-squared generated 0.767 that mean variable dependent can be explained by four independent as much 76% and the 24% with other variable outside research.keywords : Productive zakat, BAZNAS, SMEs